Analisis Kualitatif Konsep Seksualitas dalam Al-Qur’an dan Hadis - SALMA SALMA; BENI FIRDAUS (Fakultas Agama Islam Universitas Muhammadiyah Yogyakarta, 2016)
This study is about the concept of sexuality in the Qur‘an and Hadith. The concept of sexuality is one of the topics rarely discussed by Muslims. Topics on sexuality are sill regarded as dirty and taboo. Sexulaity is merely seen among the majority of society as a sexual intercourse between man and woman. This article seeks to uncover the concept of sexuality in al-Qur‘an and Hadith by examining some Quranic terms and concepts and linking those terms/concepts. This research utilizes content analysis and proportional analysis units. The author argues that the concepts of sexuality in Islamic literature is not a taboo given that al-Qur‘an and Hadith mentioned and discussed sexuality from various aspects, including physi- ological and psichological aspects